Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18178958
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Traits of Patients with Coexistent Inflammatory Bowel Disease and Periodontal Disease: A Systematic Review

Abstract: This systematic review assessed studies that evaluated the immunological traits of patients with both inflammatory bowel disease (IBD) and periodontal disease. An electronic search for literature was conducted on PubMed, Embase, Scopus, Cochrane and Web of Science. Studies that evaluated the immunological response in patients with IBD and periodontal disease were considered eligible for inclusion. A total of 6 cross-sectional studies of 275 patients were included. Immunological analyses were performed in gingi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Since periodontal disease can cause endodontic pathology and make RCT necessary, the higher prevalence of RFT in IBD patients demonstrated in the present study could also be explained by the higher prevalence of periodontal disease associated with IBD patients (Koutsochristou et al, 2015; Zhang et al, 2020). The coexistence of IBD and periodontal disease seems to be associated with a more responsive inflammatory reaction compared with individuals having one or the other (de Mello‐Neto et al, 2021). Nevertheless, in the present study, the proportion of patients with periodontal disease was similar in the two groups compared.…”
Section: Discussionmentioning
confidence: 99%
“…Since periodontal disease can cause endodontic pathology and make RCT necessary, the higher prevalence of RFT in IBD patients demonstrated in the present study could also be explained by the higher prevalence of periodontal disease associated with IBD patients (Koutsochristou et al, 2015; Zhang et al, 2020). The coexistence of IBD and periodontal disease seems to be associated with a more responsive inflammatory reaction compared with individuals having one or the other (de Mello‐Neto et al, 2021). Nevertheless, in the present study, the proportion of patients with periodontal disease was similar in the two groups compared.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al found that long-term antibiotic use led to gut ecological dysbiosis, which increased periodontitis-associated pathogens in the oral cavity and decreased oral microbiota probiotics associated with periodontal health, while Th17 cellassociated pro-inflammatory cytokine (IL-17A, IL-6) expression was upregulated and Treg cell-associated cytokine (Foxp3 and IL-10) expression was decreased in periodontal tissues; in contrast, the use of fecal microbiota transplantation (FMT) not only restored the intestinal microbiota of the mice, but even reversed the Th17/Treg imbalance in periodontal tissue and alleviated periodontitis (Yuan et al, 2023). Katarzyna et al found elevated levels of IL-1b, IL-6 and TNF by measuring salivary inflammatory markers in patients with IBD, with elevated levels of TNF-a and IL-6 being strongly associated with the development of periodontitis (Szczeklik et al, 2012); in the Figueredo team's study, inflammation scores in gingival tissue were significantly higher in patients with active IBD (including four cytokines, IL-1b, IL-6, IL-21 and sCD40L) (Figueredo et al, 2017); nevertheless, anti-inflammatory factors such as IL-4 decrease with increasing levels of inflammation, and IL-4 levels were found to be significantly lower in the gingival sulcus of IBD patients with periodontitis (de Mello-Neto et al, 2021). This evidence suggests that IBD may be closely associated with the development of periodontitis by decreasing the immune defenses of periodontal tissues.…”
Section: Immune Mechanism Associations Of Periodontitis and Ibdmentioning
confidence: 99%
“…Similar to IBD, periodontitis is a multifactorial condition where a chronic inflammatory response is triggered and maintained by genetic and environmental factors 4 . In addition, patients with both IBD and periodontal disease have been shown to have a hyperinflammatory response compared with individuals with IBD or periodontal disease alone 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, patients with both IBD and periodontal disease have been shown to have a hyperinflammatory response compared with individuals with IBD or periodontal disease alone. 5,6 The use of animal models has contributed significantly to elucidating the pathogenesis of both IBD and periodontitis. 7,8 The dextran sulphate sodium (DSS)-induced colitis (DIC) model is generally accepted as one of the best methods to study IBD because it mirrors symptoms of human IBD, such as bloody faeces, diarrhoea, weight loss, mucosal ulceration and intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%